Information literacy and social justice : radical professional praxis - Gregory, Lua; Higgins, Shana (Library Juice Press, 2013)
"Discusses information literacy and its social justice aspects, through a selection of chapters addressing the values of intellectual freedom, social responsibility, and democracy in relation to the sociopolitical context of library work"--Provided by publisher.